How smart should a forager be?. (1st March 2022) - Bhat, U; Redner, S
Abstract: We introduce an idealized model of an intelligent forager in which higher intelligence corresponds to a larger spatial range over which the forager can detect food. Such a forager diffuses randomly whenever the nearest food is more distant than the forager's detection range, R, and moves ballistically towards the nearest food that is inside its detection range. Concomitantly, the forager's metabolic energy cost per step is an increasing function of its intelligence. A dumb forager wanders randomly and may miss nearby food, thus making it susceptible to starvation. Conversely, a too-smart forager incurs a large metabolic cost per step during its search for food and is again susceptible to starvation. We show that the forager's lifetime is maximized at an optimal, intermediate level of intelligence.